Neuroprotective effects of ascorbic acid against 3-NP induced Huntington’s disease in experimental rats - Dharmender Jaglan, Dharmender Jaglan; Chanpreet Singh, Chanpreet Singh (International Journal of Indigenous Herbs and Drugs, 2017)
Objective: The present study was designed to evaluate the neuroprotective effects of ascorbic acid against 3-nitropropionic acid (3-NP) induced huntington’s disease [HD] in rats and possible involvement of GABAA receptors.Methods: 3-nitropropionic acid (10 mg/kg) was administered intraperitoneally (i.p) once daily for a period of 14 days to induce the symptoms of HD. In this study bicuculline was employed as an antagonist to confirm the involvement of GABA receptor. All the behavioural parameters were observed before drug administration and 24 hrs after first dose and 24 hrs after the last dose, that on the 15th day after the start of 3-NP treatment.Results: Administration of ascorbic acid (200 mg/kg, i.p.) per se had no effect on acquisition, memory, motor activity and various biochemical parameters as compared to control group animals. Pre-treatment with ascorbic acid (100 mg/kg and 200 mg/kg, i.p.) once daily for a period of 14 days attenuated 3-NP induced motor and cognitive impairement together with improvement in biochemical parameters (↑GSH, ↓ MDA, ↓ AChE, ↓ MPO& ↓ iNOS) in a dose dependent manner in rats. Pre-treatment with bicuculline (1 mg/g, i.p.) once daily for a period of 14 days abolished the neuroprotective effects of ascorbic acid on 3-NP treated rats. In addition, histopathological changes in present study have further justified the approach.Conclusion: The results of the present study demonstrate that ascorbic acid has shown neuroprotective effects against 3-NP induced behavioural and biochemical alterations similar to Huntington’s disease in rats and the said role of ascorbic acid involves the activation of GABAA receptors..